Caracterização quali-quantitativa da água do Rio Cascavel - Covatti, Joane Aura Cechet (2006)
This work had as objective characterizes the water of the basin hydrographic of the Cascavel River, in their quali-quantitative aspects. The river that is born in the urban area, includes an area of drainage of 50,11 Km2 and he/she has a length of 17,5 km. With maximum altitude of 767 m, minimum altitude of 18 m and a flow of 973,00 m3/h and flow of reception 345,00 m3/h. Her geographical location is among the parallel ones 24o32' and 25o17' of South latitude and the meridians 53o05' and 53o50' of longitude West. The focus of this study is the spring basin that has their East, in the area of the municipal lake, until the point of reception of water of the Company of Sanitation of Paraná - SANEPAR, before the point of affluence of the Quati River and of the Peroba River and deságüe in Andrade River. For the quantitative analysis, a vertical ruler was used in the water (linímetro) and regular observation of the level, in the section of exit of the study area. For the space qualitative analysis, a method of collections periodic samples of the turbidez parameters, color, pH, MO, Nitrate, DBO, DQO, total solids and match, in 4 points, along Cascavel River, in the period: of March of 2004 to May of 2006. For the temporary qualitative analysis a method of collections of daily samples was used, in the period of January of 2004 to May of 2006, of the turbidez parameters, color, pH, MO, alkalinity and iron, in the point of collection 4 - Reception of SANEPAR, with base in the suitable methodologies for the Standard Methods. The parameters used for analyses were them based in the use of the body hidric, aided by the legislation that establishes classification and monitoramento, of the bodies hidrics, Resolution Conama 357/2005. The analysis of the results showed that there is variability in the flow of the river, for factors that you/they also commit the environmental quality, such as: retreat of the vegetable covering, waterproofing of the soil for the occupation of the environs and garbage release, added to the sanded. Those results, in her width, they can come to be used as instrument for the definition of priorities as for the guidelines to subsidize a program of administration hydrologic and for the establishment of united actions to preserve, to revitalize or to revert the environmental damages of the spring in the Cascavel River, because they favor the economical-social impact for the price of the tariff of water of SANEPAR, that tends to increase as adult is the application of chemical products in the clarification of the water, to be used in the public provisioning.